Fluctuations in age structure and their variable influence on population growth. (30th August 2019) - Hoy, Sarah R.; MacNulty, Daniel R.; Smith, Douglas W.; Stahler, Daniel R.; Lambin, Xavier; Peterson, Rolf O.; Ruprecht, Joel S.; Vucetich, John A.
Abstract: Temporal fluctuations in growth rates can arise from both variation in age‐specific vital rates and temporal fluctuations in age structure (i.e. the relative abundance of individuals in each age‐class). However, empirical assessments of temporal fluctuations in age structure and their effects on population growth rate are relatively rare. Most research has focused on understanding the contribution of changing vital rates to population growth rates and these analyses routinely assume that: (a) populations have stable age distributions, (b) environmental influences on vital rates and age structure are stationary (i.e. the mean and/or variance of these processes does not change over time), and (c) dynamics are independent of density. Here we quantified fluctuations in age structure and assessed whether they were stationary for four populations of free‐ranging vertebrates: moose (observed for 48 years), elk (15 years), tawny owls (15 years) and grey wolves (17 years). We also assessed the extent that fluctuations in age structure were useful for predicting annual population growth rates using models which account for density dependence. Fluctuations in age structure were of a similar magnitude to fluctuations in abundance. For three populations (moose, elk, owls), the mean and the skew of the age distribution fluctuated without stabilizing over the observed time periods. More precisely, the sample variance (interannual variance) of age structure indices increased with the length of the study period, which suggests that fluctuations in age structure were non‐stationary for these populations – at least over the 15‐ to 48‐year periods analysed. Fluctuations in age structure were associated with population growth rate for two populations. In particular, population growth varied from positive to negative for moose and from near zero to negative for elk as the average age of adults increased over its observed range . Non‐stationarity in age structure may represent an important mechanism by which abundance becomes non‐stationary – and therefore difficult to forecast – over time‐scales of concern to wildlife managers. Overall, our results emphasize the need for vertebrate populations to be modelled using approaches that consider transient dynamics and density dependence and that do not rely on the assumption that environmental processes are stationary. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.